Numerical simulation of saltwater intrusion in Panglao Island, Bohol - Cleofas, Dolores SD (2012)
Saltwater intrusion is a common groundwater-quality issue in many coastal areas. It happens when the underlying seawater is pumped together with freshwater when the existing freshwater sources are excessively extracted . Under certain conditions, when salt water moves vertically upward, a stable cone in the freshwater-saltwater interface develops at some depth in the bottom of the well, and the well still discharges fresh water. For the unstable condition the interface rises abruptly towards the well, causing salinity. This phenomenon becomes more complicated when the aquifer is karstic like that of Bohol where the study area is located. The FEMWATER which is a finite element, three-dimensional groundwater flow and salinity transport model is used in this study to investigate the saltwater intrusion problem of Panglao, Island, Bohol, Philippines. Dirichlet or constant head boundary conditions are applied to flow at the peripheral boundaries of the island representing tidal elevation of the sea while variable boundary conditions at the surface and at the base due to rainfall and groundwater pumping. For salinity transport, constant boundary conditions are applied at the surface since rainfall is assumed free of saltwater, constant boundary conditions at the sides because of sea water and variable boundary conditions at the bottom because of pumping. Model calibration involved three sets of groundwater salinity data measured during the investigation period. The water samples were taken from twenty-eight deepwells in Panglao Island. Based on these data, the calibrated hydraulic conductivity is found to be 3,000 m/day (being a karstic area) and varying elevation of saltwater upconing for each of the sampling points. The calibrated model reproduces the behaviour of the aquifer quite well and could be used to simulate a number of management options.